Pythagorean Fuzzy Set and Its Application to Determining Student Concentration Using Max-Min-Max Composition - Nuur, Imam Hafiidz; Munandar, Arif (Journal of Fundamental Mathematics and Applications (JFMA), 2024)
Pythagorean fuzzy set is a generalization of intuitionistic fuzzy set. As intuitionistic fuzzy set that can be used to help in solving problems regarding decision making, pythagorean fuzzy set can also be done for the same thing.  In the pythagorean fuzzy set, a max-min-max composition relation will be formed and used it to solve decision-making problems. Through this research, decision making in determining the concentration for students of the Mathematics undergraduates program at Sunan Kalijaga State Islamic University Yogyakarta is discussed based on data on student grades in compulsory courses that have been taken by students until the 4th semester. Concentration that is in line with the interests and abilities is expected to facilitate the writing of the student's final project.